Research on Improved Ray Casting Algorithm and Its Application in Three-Dimensional Reconstruction - ZheShu Jia; DeYun Chen; Bo Wang (Shock and Vibration)
Spinal pathology treatment has become an urgent issue to be solved. How to effectively prevent and treat spinal pathology has become a research hotspot in the field of surgery. Aiming at the problem of too long volume rendering time caused by the trilinear interpolation sampling method in the reconstruction and visualization of the vertebra 3D model, an improved ray projection algorithm is proposed to quickly reconstruct a 3D vertebra model from medical CT vertebra images. This method first classifies CT data, assigns corresponding color values and opacity transfer functions to different types of data, and then uses inverse distance-weighted interpolation (IDWI) sampling to replace the trilinear interpolation sampling method for the voxel where the sampling point is located to accelerate the interpolation operation. The color value and opacity of the sampling points are obtained, and finally, the attributes of all the sampling points are synthesized and calculated to obtain the final rendering effect, and the reconstruction of the three-dimensional vertebra model is completed. Experimental results show that the proposed method not only can obtain higher quality rendered images but also has a certain improvement in rendering speed compared with traditional algorithms.